Uncle Snow Enterprise: homemade ice cream / Muhamad Arif Aizat Zulkefle ...[et al.] - Zulkefle, Muhamad Arif Aizat; Abdul Razak, Nur Ashikin; Saipulazam, Nurul Ashikin; Kahar, Nurul Ashiqin; Adam Suboh, Siti Nur Hajar (2014)
We planned to do this business because there are huge opportunities to combine all the homemade ice cream products is one side which come out as 'Uncle Snow'.